New Mn(II), Ni(II), Cd(II), Pb(II)complexes with 2-methylbenzimidazole and other ligands. synthesis, spectroscopic characterization, crystal structure, magnetic susceptibility and biological activity studies - Shaker, S.A.; Ali, Hapipah Mohd; Cheah, S.C.; Khaledi, H. (2012)
Synthesis and characterization of Mn(II), Ni(II), Cd(II) and Pb(II) mixed ligand complexes of 2-methylbenzimidazole with other ligands have been reported. The structure of the ligands and their complexes was investigated using elemental analysis, IR, UV-Vis, ( 1H, 13C) NMR spectroscopy, molar conductivity and magnetic susceptibility measurements. In all the studies of complexes, the 2-methylbenzimidazole behaves as a neutral monodentate ligand which is coordinated with the metal ions through the N atom. While benzotriazole behaves as a neutral bidentate ligand which is coordinated with the Ni(II) ion through the two N atoms. Moreover, the N-acetylglycine behaves as a bidentate ligand which is coordinated with the Mn(II), Ni(II) and Pb(II) ions through the N atom and the terminal carboxyl oxygen atom. The magnetic and spectral data indicate the tetrahedral geometry for Mn(II) complex, irregular tetrahedral geometry for Pb(II) complex and octahedral geometry for Ni(II) complex. The X-ray single crystal diffraction method was used to confirm a centrosymmetric dinuclear Cd(II) complex as each two metal ions are linked by a pair of thiocyanate N = S bridge. Two 2-methylbenzimidazole N-atom donors and one terminal thiocyanate N atom complete a highly distorted square pyramid geometry around the Cd atom. Besides, different cell types were used to determine the inhibitory effect of Mn(II), Ni(II), Cd(II) and Pb(II) complexes on cell growth using MTT assay. Cd(II) complex showed cytotoxic effect on various types of cancer cell lines with different EC 50 values. © 2012.